AN ANALYSIS OF STUDENT’S PROBLEM IN WRITING ERROR IN THE USE OF SIMPLE PAST ON RECOUNT TEXT AT 10th GRADE MA DARUL ULUM TLASIH - Meidina Uzlifatul Jannah; Ruri Fadilah, S.Hum, M.Pd (ETNOLINGUAL, 2022)
Abstract This study analyzes simple past tense errors in MA Darul Ulum Tlasih by analyzing the types of errors in the use of simple past tense in recount text. This research is expected to help in developing English learning to process and provide information in order to increase knowledge to understand the mistakes made in the use of the simple past tense. This study uses an approach that is carried out in several stages: preparation is carried out by providing an explanation of the simple past tense. The data were taken from the 10th grade students of MA Darul Ulum Tlasih by providing a working instrument to make a recount text of a personal experience. The author uses several data analysis techniques, namely: error, classification, description, and correction. The results of this show students' errors in misinformation and misodering. Keywords: Simple past tense, eror analysis, omission, misinformation, misodering, and recount text.